Charge Density Influences C1 Domain Ligand Affinity and Membrane Interactions. Issue 8 (28th April 2014) - Kelsey, Jessica S.; Geczy, Tamas; Lewin, Nancy E.; Kedei, Noemi; Hill, Colin S.; Selezneva, Julia S.; Valle, Christopher J.; Woo, Wonhee; Gorshkova, Inna; Blumberg, Peter M.
Abstract The C1 domain, which represents the recognition motif on protein kinase C for the lipophilic second messenger diacylglycerol and its ultrapotent analogues, the phorbol esters, has emerged as a promising therapeutic target for cancer and other indications. Potential target selectivity is markedly enhanced both because binding reflects ternary complex formation between the ligand, C1 domain, and phospholipid, and because binding drives membrane insertion of the C1 domain, permitting aspects of the C1 domain surface outside the binding site, per se, to influence binding energetics. Here, focusing on charged residues identified in atypical C1 domains which contribute to their loss of ligand binding activity, we showed that increasing charge along the rim of the binding cleft of the protein kinase C δ C1 b domain raises the requirement for anionic phospholipids. Correspondingly, it shifts the selectivity of C1 domain translocation to the plasma membrane, which is more negatively charged than internal membranes. This change in localization is most pronounced in the case of more hydrophilic ligands, which provide weaker membrane stabilization than do the more hydrophobic ligands and thus contributes an element to the structure–activity relations for C1 domain ligands. Coexpressing pairs of C1‐containing constructs with differing charges each expressing a distinct fluorescent tag provided a powerful tool to demonstrate the effect of increasing charge in the C1 domain.